Gestational diabetes is associated with high energy and saturated fat intakes and with low plasma visfatin and adiponectin levels independent of prepregnancy BMI - Park, S; Kim, M-Y; Baik, S H; Woo, J-T; Kwon, Y J; Daily, J W; Park, Y-M; Yang, J-H; Kim, S-H (European journal of clinical nutrition, 2013)
Background/Objectives: Gestational diabetes mellitus (GDM) risk factors are well established for Caucasians, but not for Asians. We hypothesized that nutrient intakes, plasma adipokines and/or gestational hormones might be linked to GDM development among pregnant Korean women. This study sought to identify new risk factors for GDM and adverse pregnancy outcomes according to body weight at prepregnancy. Subjects/Methods: All subjects were pregnant women visiting the Cheil General Hospital and Women’s Healthcare Center between June 2006 and March 2009. Non-GDM ( n =531) and GDM ( n =215) participants were divided into normal-weight and overweight groups according to prepregnancy body mass index (BMI) above or below 23 kg/m 2 at 24–28th week of gestation. At that time, glucose tolerance, insulin resistance as homeostatic model assessment for insulin resistance, insulin secretory capacity as homeostatic model assessment for β-cell function, anthropometric measurement, nutrient intakes, and plasma levels of adipokines and gestational hormones were determined. Results: GDM women gained more weight in early pregnancy than non-GDM among normal-weight women. GDM was mainly associated with increased insulin resistance in overweight women and decreased insulin secretory capacity in normal-weight women. Plasma visfatin and adiponectin were lower and progesterone levels higher in GDM than non-GDM independent of BMI while plasma resistin levels were higher in non-GDM, but not GDM, overweight women. Energy and saturated fat intakes were higher in GDM independent of body weight, whereas taurine intakes were lower in GDM than non-GDM only in normal-weight women. Conclusions: Low visfatin and adiponectin and high progesterone levels in the circulation and high energy and saturated fat intakes were common risk factors for GDM and pregnancy outcome such as large for gestational age. Daily reference intakes for energy and fat during pregnancy need to be re-evaluated according to prepregnancy BMI.